Constructing collectivity : 'we' across languages and contexts - Pavlidou, Theodossia (Pragmatics & beyond new series, 2014)
This chapter examines the referential domain, communicative function and perlocutionary effect of the first person plural pronoun we in dialogic and monologic British political discourse. Its methodological framework is an integrated one, combining interactional sociolinguistics, in particular co-occurrence and conversational inference, with quantitative and qualitative corpus analysis. The first part presents the methodological framework, focussing on the two types of discourse and the genre-specific distribution of self-references expressing collectivity considering the pronoun we and possib.